2014
DOI: 10.1111/gcb.12595
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation in nitrous oxide emissions from perennial ryegrass/white clover grassland used for dairy production

Abstract: Nitrous oxide (N2O) emissions are subject to intra- and interannual variation due to changes in weather and management. This creates significant uncertainties when quantifying estimates of annual N2O emissions from grazed grasslands. Despite these uncertainties, the majority of studies are short-term in nature (<1 year) and as a consequence, there is a lack of data on interannual variation in N2O emissions. The objectives of this study were to (i) quantify annual N2O emissions and (ii) assess the causes of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Interannual variability of N 2 O emissions as reported by many studies (Burchill et al ., ; Oates et al ., ), and the representativeness of the study period, limit the generalization of these results. The study period had a wet early summer (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Interannual variability of N 2 O emissions as reported by many studies (Burchill et al ., ; Oates et al ., ), and the representativeness of the study period, limit the generalization of these results. The study period had a wet early summer (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…For 2 consecutive years, they obtained annual emissions of 0.55 and 0.44 g N m −2 , respectively, bracketing the result for the IFR site. Burchill et al (2014) found, for a rotationally grazed and intensively fertilised ryegrass pasture in Ireland, annual N 2 O emissions over 4 years to range from 0.44 to 3.44 g N m −2 . The annual emissions from the IFR site are within this range, near the lower end.…”
Section: N 2 O Emissions and Nitrogen Inputsmentioning
confidence: 97%
“…The annual emissions from the IFR site are within this range, near the lower end. Burchill et al (2014) also measured the annual emissions from ungrazed, unfertilised ryegrass pasture. These ranged from 0.17 to 0.63 g N m −2 , i.e.…”
Section: N 2 O Emissions and Nitrogen Inputsmentioning
confidence: 99%
“…Burchill et al . () reported that winter N 2 O emissions from a pasture soil were low when soils were poorly drained because in winter, evaporation is low and thus poorly drained soils are more likely to be completely saturated resulting in greater N 2 O reductase activity (Hamonts et al . ; Hansen et al .…”
Section: Factors Controlling the Magnitude Of N2o Emissions From Grazmentioning
confidence: 99%
“…Similarly, Burchill et al . () continuously measured the N 2 O emissions from a pasture for 3 years and observed winter N 2 O emissions were higher after an unusually cold period (maximum daily air temperature was <0°C for a period of 6 days) with soil freeze/thaw events. During a normal year, the maximum daily temperature remains above 0°C even during winter at this experimental site although the minimum daily temperature was <0°C for winter in a normal year.…”
Section: Factors Controlling the Magnitude Of N2o Emissions From Grazmentioning
confidence: 99%